Alcohol‐associated intestinal dysbiosis alters mucosal‐associated invariant T‐cell phenotype and function. (3rd April 2021) - Gu, Min; Samuelson, Derrick R.; Taylor, Christopher M.; Molina, Patricia E.; Luo, Meng; Siggins, Robert W.; Shellito, Judd E.; Welsh, David A.
Abstract: Background: Chronic alcohol consumption is associated with a compromised innate and adaptive immune responses to infectious disease. Mucosa‐associated invariant T (MAIT) cells play a critical role in antibacterial host defense. However, whether alcohol‐associated deficits in innate and adaptive immune responses are mediated by alterations in MAIT cells remains unclear. Methods: To investigate the impact of alcohol on MAIT cells, mice were treated with binge‐on‐chronic alcohol for 10 days and sacrificed at day 11. MAIT cells in the barrier organs (lung, liver, and intestine) were characterized by flow cytometry. Two additional sets of animals were used to examine the involvement of gut microbiota on alcohol‐induced MAIT cell changes: (1) Cecal microbiota from alcohol‐fed (AF) mice were adoptive transferred into antibiotic‐pretreated mice and (2) AF mice were treated with antibiotics during the experiment. MAIT cells in the barrier organs were measured via flow cytometry. Results: Binge‐on‐chronic alcohol feeding led to a significant reduction in the abundance of MAIT cells in the barrier tissues. However, CD69 expression on tissue‐associated MAIT cells was increased in AF mice compared with pair‐fed (PF) mice. The expression of Th1 cytokines and the corresponding transcriptional factor was tissue specific, showing downregulation in the intestine and increases in the lung and liver in AF animals. Transplantation of fecal microbiota from AF mice resulted in a MAIT cell profile aligned to that of AF mouse donor. Antibiotic treatment abolished the MAIT cell differences between AF and PF animals. Conclusion: MAIT cells in the intestine, liver, and lung are perturbed by alcohol use and these changes are partially attributable to alcohol‐associated dysbiosis. MAIT cell dysfunction may contribute to alcohol‐induced innate and adaptive immunity and consequently end‐organ pathophysiology. Abstract : Chronic alcohol binge reduces mucosa‐associated invariant T (MAIT) cell count, increases CD69 expression and alters expression of Th1 cytokines and transactional factors in mucosal‐related tissues. Alcohol naïve mice reconstituted with cecal microbiota from alcohol‐fed animals show a similar MAIT cell profile with alcohol‐fed mice. Meanwhile, antibiotic treatment abolishes the effect of alcohol on MAIT cell profile in mice. These results suggest that MAIT cell changes induced by alcohol use are partially attributable to alcohol‐associated dysbiosis.